2006
DOI: 10.1124/dmd.106.009381
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Carboxylesterase Isozymes and Their Contribution to Hydrolase Activity in Human Liver and Small Intestine

Abstract: ABSTRACT:Hydrolase activity from human liver and small intestine microsomes was compared with that of recombinant human carboxylesterases, hCE-1 and hCE-2. Although both hCE-1 and hCE-2 are present in human liver, the dominant component was found to be hCE-1, whereas the hydrolase activity of the human small intestine was found to be predominantly hCE-2. hCE-2 has a limited ability to hydrolyze large acyl compound substrates. Interestingly, propranolol derivatives, good substrates for hCE-2, were easily hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
173
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 235 publications
(188 citation statements)
references
References 23 publications
12
173
0
2
Order By: Relevance
“…It includes human intestinal CE (CES2A1), 34,[40][41][42][43][44] rat CES2 (CES2A10), 22) rat intestinal CE RL4 (rCES2) (CES2A6), 45) rabbit form 2 46) and hamster AT51 (CES2A11). 47) CES3 includes ES-male (CES3A2) and human CES3 (CES3A1).…”
Section: Novel Classification and Nomenclature Of Mammalian Cesunclassified
See 1 more Smart Citation
“…It includes human intestinal CE (CES2A1), 34,[40][41][42][43][44] rat CES2 (CES2A10), 22) rat intestinal CE RL4 (rCES2) (CES2A6), 45) rabbit form 2 46) and hamster AT51 (CES2A11). 47) CES3 includes ES-male (CES3A2) and human CES3 (CES3A1).…”
Section: Novel Classification and Nomenclature Of Mammalian Cesunclassified
“…Most of the CES1 families, except CES1G, are mainly expressed in the liver. The CES 1A subfamily includes the major forms of human CEs, 18,19,34,[36][37][38] and the major isoforms of rat, 9) dog, 19) rabbit 37) and mouse 35) CE. The CES1B subfamily includes the major isoforms of rat, 9) mouse 20) and hamster 47) CE, and CES1C includes the major isoforms of dog, 18,19) cat 50) and human 38) CE.…”
Section: Novel Classification and Nomenclature Of Mammalian Cesmentioning
confidence: 99%
“…4). Actually, it has been shown that dog CES1 isozyme was involved in a pulmonary first-pass effect in the disposition of a propranolol ester prodrug (Imai, 2006;Imai et al, 2006). It has also been shown that the expression level of the human CarbE isozyme was correlated with the conversion ratio of CPT-11 to SN-38, the active metabolite, which is thought to be a key step for the chemotherapeutic action of this anti-tumor drug (Pindel et al, 1997;Zhang et al, 2002;Ohtsuka et al, 2003;Sanghani et al, 2003).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…It includes human intestinal CarbE (CES2A1) (Schwer et al, 1997;Humerickhouse et al, 2000;Imai et al, 2006;Taketani et al, 2007;Yang et al, 2007;Shi et al, 2008), rCES2 (CES2A10) (Furihata et al, 2005), rat intestinal CarbE RL4 (rCES2) (CES2A6) (Furihata et al, 2003), rabbit form 2 (Ozols, 1989) and hamster AT51 (CES2A11) (Sone et al, 1994). CES3 includes ES-male (CES3A2) and human CES3 (CES3A1) (Aida et al, 1993;Sanghani et al, 2004).…”
Section: Introductionunclassified
See 1 more Smart Citation